-29-6x=-5(-5x+1)-7x

Simple and best practice solution for -29-6x=-5(-5x+1)-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -29-6x=-5(-5x+1)-7x equation:


Simplifying
-29 + -6x = -5(-5x + 1) + -7x

Reorder the terms:
-29 + -6x = -5(1 + -5x) + -7x
-29 + -6x = (1 * -5 + -5x * -5) + -7x
-29 + -6x = (-5 + 25x) + -7x

Combine like terms: 25x + -7x = 18x
-29 + -6x = -5 + 18x

Solving
-29 + -6x = -5 + 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
-29 + -6x + -18x = -5 + 18x + -18x

Combine like terms: -6x + -18x = -24x
-29 + -24x = -5 + 18x + -18x

Combine like terms: 18x + -18x = 0
-29 + -24x = -5 + 0
-29 + -24x = -5

Add '29' to each side of the equation.
-29 + 29 + -24x = -5 + 29

Combine like terms: -29 + 29 = 0
0 + -24x = -5 + 29
-24x = -5 + 29

Combine like terms: -5 + 29 = 24
-24x = 24

Divide each side by '-24'.
x = -1

Simplifying
x = -1

See similar equations:

| Sinx=3 | | 2b+58b=35 | | -21+5+-9=3(t-4)-5 | | 71=6(4n-8)-7n | | 2(x-5)=3(x-1) | | s+6=78 | | 2x+3y-5x+5y= | | 5(1+6a)=-39+8a | | 2+2v=-2 | | 2z^3+9z^2=5z | | 5b-16-8n=-10 | | 7(y+1)=49 | | K=17 | | X+3=-32 | | 15-f=-23 | | 4-5(x+3)=25 | | -22+7r=6(r-4) | | 3x+7+6x+11=90 | | 4x+1=11x | | -2(5y+5)=4 | | 3*x=10 | | 8+16=-3(5x-8) | | 9(6x-5)=279 | | 22x-16x+12=-15+3x+12+6x | | 5x-9=13-x | | 7=20 | | 120*24= | | -30+5n=4+4(1+6n) | | -4(x+8)=-3x-5 | | 4(y+5)=-6(2y-1)+4y | | x^2+8x+8=o | | -5x=5x-100 |

Equations solver categories